Strategi Pengembangan Dalam Meningkatkan Daya Tarik Wisatawan Di Watu Bayang Desa Klangon Kecamatan Saradan Kabupaten Madiun - Angga Pramodya Pradhana; Anik Tri Haryani; Krista Yitawati (Universitas Merdeka Madiun, 2020)
Abstractâ€” This community service is done by the author in order to carry out one of the tasks of Tridharma as a lecturer, by helping develop Watu Bayang Tourism in Klangon Village, Saradan District, Madiun Regency. The method I use is to provide information to the Klangon village community about the development strategy in increasing tourist attraction, conducting technology training to the community in promoting Watu Bayang tourism through social media and coordinating with village governments, local governments and communities in managing tourism villages in Klangon Village. The result was obtained a strategy to develop the potential of Watu Bayang tourism area so that it could lift the shadow rock tourism area and improve the economy of the Klangon village community.Â Keywordsâ€”: Strategy; Attraction; Tourism.